Bond performance between textile reinforced concrete (TRC) and brick masonry under conventional environment. (February 2022) - Shiping, Yin; Boxue, Wang; Chenxue, Zhang; Shuang, Liu
Abstract: The interfacial bonding properties between textile-reinforced concrete (TRC) and masonry substrate is one of the critical indicators to evaluate the strengthening effectiveness. The effects of textile type, matrix type and interfacial bond length on the bond properties between TRC and masonry were analyzed according to single shear test in this paper; especially, engineered cementitious composite (ECC) was considered as the matrix to improve material properties. Failure mode, load-slip response, failure mechanism, bond properties and fracture energy between TRC and masonry were analyzed. The results showed that failure mode is influenced on the textile types and textile slippage from the matrix is the most common failure mode which may be accompanied by tensile rupture of textile. The bond properties between TRC and masonry using coated-carbon textile was the best. The ultimate load and bond strength are the largest when the bond length exceeds the effective bond length. The effective bond length is related to the textile and the matrix type, the effective bond length under different conditions is obtained. The fracture energy is obtained and its influencing factors are analyzed in this paper.